2023
DOI: 10.1097/anc.0000000000001074
|View full text |Cite
|
Sign up to set email alerts
|

A Quality Improvement Pilot Project for Noise Reduction in the NICU

Abstract: The sounds that infants in utero are exposed to are muffled and dampened by amniotic fluid and the uterine wall. 1 This decrease in noise allows the infant brain to grow as needed, without interruption. 2 When a healthy term infant is born, the infant can process external stimuli without negative physiologic effects occurring. This is not the case for all infants. Premature and critically ill infants are at increased risk of negative effects related to noxious external stimuli, due to the activation of autonom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
(221 reference statements)
0
4
0
Order By: Relevance
“…2,4,5,31 To address this problem, several approaches have been reported to promote a "culture of silence" and increase protected sleep, including quiet time protocols, staff education programs, visual noise feedback monitors, and staff "sound compliance supervisors". 3 , 5 , 10 , [32][33][34][35][36][37] Ongoing staff education programs, coupled with monitoring noise levels, are essential to sustaining a commitment to noise reduction in the NICU. Parents and family members can also be supported to engage in developmentally appropriate care to become competent caregivers and advocates for the neuroprotection of their babies.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…2,4,5,31 To address this problem, several approaches have been reported to promote a "culture of silence" and increase protected sleep, including quiet time protocols, staff education programs, visual noise feedback monitors, and staff "sound compliance supervisors". 3 , 5 , 10 , [32][33][34][35][36][37] Ongoing staff education programs, coupled with monitoring noise levels, are essential to sustaining a commitment to noise reduction in the NICU. Parents and family members can also be supported to engage in developmentally appropriate care to become competent caregivers and advocates for the neuroprotection of their babies.…”
mentioning
confidence: 99%
“…Parents and family members can also be supported to engage in developmentally appropriate care to become competent caregivers and advocates for the neuroprotection of their babies. [36][37][38] Craig et al reported that "parents and family members should be supported to engage in developmentally appropriate care to become competent caregivers and advocates for the neuroprotection of their babies" and that parent involvement is associated with improved neonatal outcomes. 38 , 39 In addition, quiet time protocols may significantly decrease exposure to electronic sounds and voices, increasing restful sleep and promoting growth.…”
mentioning
confidence: 99%
See 2 more Smart Citations